2012
DOI: 10.1016/j.recote.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Fresh bipolar osteochondral allograft of the ankle. Review of the literature and case report of a young patient with bilateral post-traumatic osteoarthritis

Abstract: Objectives: The treatment of severe post-traumatic ankle arthritis remains a challenge nowadays. Since patients suffering from this pathology are mainly young and active people, a correct reconstruction, if possible, of the articular cartilage defects of the tibiotalar joint is very important to achieve a good result. Fresh bipolar osteochondral allograft (FBOA) is a promising operative technique, as an alternative to arthrodesis and total ankle replacement, in pain relief, restoration of function and indefini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Studies were grouped according to surgical indications into ten categories: musculoskeletal tumours ( n = 16) [10–25], chronic ankle instability ( n = 15) [26–40], ankle arthritis ( n = 14) [41–54], osteochondral lesions of the talus ( n = 12) [55–66], Achilles tendon defects ( n = 11) [67–77], other tendon defects ( n = 9) [78–86], fusions ( n = 9) [87–95], fractures ( n = 8) [96–103], hallux rigidus ( n = 3) [104–106] and other indications ( n = 10) [107–116].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were grouped according to surgical indications into ten categories: musculoskeletal tumours ( n = 16) [10–25], chronic ankle instability ( n = 15) [26–40], ankle arthritis ( n = 14) [41–54], osteochondral lesions of the talus ( n = 12) [55–66], Achilles tendon defects ( n = 11) [67–77], other tendon defects ( n = 9) [78–86], fusions ( n = 9) [87–95], fractures ( n = 8) [96–103], hallux rigidus ( n = 3) [104–106] and other indications ( n = 10) [107–116].…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that an appropriate layer of cartilage from a donor can survive transplantation when supported by intact subchondral bony structure, and is progressively replaced by the host bone after surgery [18]. Although preliminary studies have reported contrasting outcomes, with about 50% of cases requiring revision following failure [20,21], more recent clinical reports have indicated that BFOA is a promising option in the treatment of posttraumatic arthritic ankles and represents a practicable alternative for younger and more active patients, where arthrodesis is not accepted and prosthetic replacement is not desired [2,22]. BFOA of the ankle is also conservative and not irreversible, thus multiple options are still available to the surgeon in case of failure [21].…”
Section: Introductionmentioning
confidence: 99%